Physical and Chemical Properties of 1-Butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide [Bmim]NTf2 Ionic Liquid - Su, Yongqing; Yang, Mingdi; Wang, Ping; Li, Cong; Cai, Ying; Ren, Nianjun (Asian Journal of Chemistry, 2011)
Some physical and chemical properties of ionic liquid 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ([Bmim]NTf2) were measured and analyzed separately. At 20 ºC, the density of [Bmim]NTf2 was 1.4682 g cm-3 and the viscosity was 56.0 m Pas. The relationship of viscosity (η) and temperature (t) was η (mPas) = 87.66-1.58 t (ºC). [Bmim]NTf2 is insoluble in water and most petroleum aromatics solvents but soluble in some molecular solvents. The conductivity was related with temperature, solvent and concentration. The conductivity increased as temperature increase or the concentration increased. [Bmim]NTf2 had excellent the chemical-stability and thermostability.